(untitled) (The Review of Diabetic Studies, 2024)
Background CRBSIs result from microbial biofilms on catheters, primarily coagulase-negative staphylococci, S. aureus, Gram-negatives, and Candida, with ICU rates of 1.8-5.2 per 1,000 catheter-days and higher in high-risk groups like hemodialysis patients. Key risks span patient factors (immunosuppression, diabetes), device characteristics (multilumen, dwell time), and procedural issues.​ Methods Narrative synthesis of contemporary literature on prevention advances, including vascular device selection (peripheral vs. central), insertion practices (ultrasound, maximal barriers, chlorhexidine), maintenance bundles (asepsis, dressings), antimicrobial innovations (coated catheters, lock solutions), and system-level interventions (training, surveillance) in diverse settings.​ Results Evidence-based bundles yield 40-60% CRBSI reductions; ultrasound guidance cuts risks by 30-35%; chlorhexidine dressings and antibiotic locks achieve 20-70% decreases; specialized teams lower rates below 1 per 1,000 catheter-days in optimized ICUs. Antimicrobial technologies show superior efficacy in prolonged-use scenarios.​ Conclusions Integrated strategies across the device lifecycle dramatically mitigate CRBSIs, though challenges persist in resource-limited contexts and with multidrug-resistant pathogens; prioritize bundle adherence, novel coatings, and tailored protocols for sustained global impact.​